Transforming Beef By-products into Valuable Ingredients: Which Spell/Recipe to Use? - Henchion, Maeve; McCarthy, Mary; O’Callaghan, Jim (Frontiers in Nutrition, 2016)
Satisfying the increasing global demand for protein results in challenges from a supply perspective. Increased use of animal proteins, through greater use of meat by-products, could form part of the solution, subject to consumer acceptance. This research investigates consumer evaluations of food products that incorporate ingredients derived from offals that have been produced through a range of food processing technologies. Using focus groups incorporating product stimuli representing various combinations of offals, processing and carrier products, the research finds that the physical state and perceived naturalness of the ingredients influences acceptance. It also highlights the impact of life experiences, linked to demographic characteristics, on interpretations and evaluations of products and processes. Ideational influences, i.e. knowledge of the nature or origin of the substance, are reasons for rejecting some concepts, with misalignment between nature of processing and the product resulting in rejection of others. Lack of perceived necessity also results in rejection. Alignment of ingredients with existing culinary practices and routines, communication of potential sensory or other benefits as well as naturalness are factors likely to promote acceptance, and generate repeat purchase, in some consumer segments. Trust in oversight that the products are safe is a prerequisite for acceptance in all cases. These findings have implications for pathways to increase sustainability of beef production and consumption through increased use of beef by-products.